Knock-Down of CsNRT2.1, a Cucumber Nitrate Transporter, Reduces Nitrate Uptake, Root length, and Lateral Root Number at Low External Nitrate Concentration - Li, Yang; Li, Juanqi; Yan, Yan; Liu, Wenqian; Zhang, Wenna; Gao, Lihong; Tian, Yongqiang (Frontiers in Plant Science, 2018)
Nitrogen (N) is a macronutrient that plays a crucial role in plant growth and development. Nitrate (NO3-) is the most abundant N source in aerobic soils. Plants have evolved two adaptive mechanisms such as up-regulation of the high-affinity transport system (HATS) and alteration of the root system architecture (RSA), allowing them to cope with the temporal and spatial variation of NO3-. However, little information is available regarding the nitrate transporter in cucumber, one of the most important fruit vegetables in the world. In this study we isolated a nitrate transporter named CsNRT2.1 from cucumber. Analysis of the expression profile of the CsNRT2.1 showed that CsNRT2.1 is a high affinity nitrate transporter which mainly located in mature roots. Subcellular localization analysis revealed that CsNRT2.1 is a plasma membrane transporter. In N-starved CsNRT2.1 knock-down plants, both of the constitutive HATS (cHATS) and inducible HATS (iHATS) were impaired under low external NO3- concentration. Furthermore, the CsNRT2.1 knock-down plants showed reduced root length and lateral root numbers. Together, our results demonstrated that CsNRT2.1 played a dual role in regulating the HATS and RSA to acquire NO3- effectively under N limitation.